The Concept of Charity in The Quran (Comparative Study of Tafsir Fi Zhilalil Qur'an and Tafsir Al-Azhar) - Ibnu Pamungkas; Arif Firdausi; Ipmawan Muhammad Iqbal (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to examine and compare the understanding of two great figures of Islam, Sayyid Qutb and Buya Hamka, in interpreting the concept of alms based on verses of the Qur'an, especially Surat Al-Baqarah verses 261 and 271. The method used is Library research with descriptive-comparative approach. Primary Data were obtained from the work of tafsir Fi Zhilalil Qur'an by Sayyid Qutb and Tafsir Al-Azhar by Buya Hamka, while secondary data came from supporting literature such as books, journals, and other scientific works. Sadaqah is a voluntary gift from a Muslim to the needy, without time and amount limits, as proof of faith and hope for a reward from Allah. In jurisprudence, Sadaqah can refer to the Giving of sunnah (alms attatawwu) or zakat, such as sadaqah al-fitr (zakat Fitr). The results showed that the two mufasir agreed on the importance of alms as a social worship that draws closer to God and benefits others. However, there are differences in the approach to interpretation: Sayyid Qutb emphasizes the spiritual and soul-building aspects of Infaq, while Buya Hamka emphasizes the practical application in social life as well as the long-term impact of alms. This difference reflects the socio-cultural and scientific background of each figure. This study is expected to be a reference in deepening the understanding of the verses of the Qur'an about alms and its application in everyday life.